Modeling of live weight per age in fattening bovines under a silvopastoral system with Leucaena leucocephala - Iraola, Jorge; García, Yenny; Muñoz, E.; Fraga, Luis M.; Barros-Rodríguez, M.; Hernández, J. L. (Cuban Journal of Agricultural Science, 2016)
The modeling of the curve of live weight per age in non-castrated male bovines under a silvopastoral system with Leucaena leucocephala during four productive cycles was evaluated. For that purpose, four genetic groups were used: Zebu, crossbred Zebu, crossbred Zebu and dairy crossbreds, with 74, 80, 90 and 90 animals, respectively. Monthly weighing was carried out in all the cycles. For deciding the goodness of fit, the following criteria were proposed: mean square of the error, fitted R2, model significance, parameter significance and graphic distribution of residues. The non-linear models (Gompertz and Logistic) were only fitted in the second and third productive cycle under the specific conditions of the study. The simple linear model showed adequate adjustments in every cycle, and showed lower values of mean square of the error than the non-linear models in the second and third cycles. There were no marked differences of liveweight increase among the four genetic groups evaluated, with daily mean gains around and superior to 0.700 kg. This indicates the need of developing specific strategies for the ending stages of male bovines under silvopastoral conditions. Further studies on modeling with higher liveweight at sacrifice of Zebu and crossbred animals are suggested, which will allow to predict the productiveperformance of these animals. Interpreting the results and controlling the indicators, like food balance and management, could substantially improve the indicators of liveweight at sacrifice in a silvopastoral system with leucaena and grasses.Key words: linear and non-linear model, bovines, silvopastoral system